Chemical composition and in vitro digestibility of fresh sugarcane hydrolysed with calcium oxide (CaO) - Domingues, Felipe Nogueira; Oliveira, Mauro Dal Secco de [UNESP]; Mota, Diego Azevedo; Santos, Juliana dos; Miranda, Augusto Sousa; Oliveira, Raimundo Parente de (Univ Estadual Londrina, 2015)
The objective was to evaluate the chemical composition and in vitro digestibility of sugarcane hydrolysed with increasing doses of calcium oxide and varying air exposure times. A completely randomised, split plot design was used; the doses were allocated to the plots, and the air exposure times were allocated to the subplots, with four repetitions. The data underwent analysis of variance and were laid out according to the effect of the treatment on the components of polynomial regressions, and evaluated at the 5% probability. The increase in the dosage negatively affected the quantities of neutral-detergent fibre (NDF), acid-detergent fibre (ADF), lignin (LIG), total carbohydrates (TC), cellulose (CEL), crude protein (CP), and ether extract (EE); and positively affected the quantities of non-fibrous carbohydrates (NFC) and mineral matter (MM). The addition of calcium oxide improved the in vitro digestible dry matter (IVDMD) coefficients and was able to keep up to 72 hours. The in vitro digestibility of the neutral-detergent fibre (IVDNDF) and of the acid-detergent fibre (IVDADF) coefficients decreased when calcium oxide was added. Calcium oxide has the ability to hydrolyse the fibrous fraction and conserve chopped sugarcane. Doses of 0.5 and 1.0% lime exhibited similar results to those achieved at higher doses; therefore, higher doses are not required in the hydrolyses of sugarcane. Over time, the sugarcane deteriorates, but this deterioration is reduced by the addition of calcium oxide.

Objetivou-se avaliar a composição bromatológica e a digestibilidade in vitro da cana-de-açúcar hidrolisada com doses crescentes de óxido de cálcio e diferentes tempos de exposição ao ar. Utilizouse o delineamento inteiramente casualizado, em esquema de parcelas subdivididas, sendo as doses alocadas nas parcelas e os tempos de exposição ao ar nas subparcelas, com quatro repetições. Os dados foram submetidos à análise de variância e desdobrados quanto ao efeito de tratamento nos componentes de regressões polinomiais, e avaliados a 5% de probabilidade. A elevação das doses influenciou negativamente os teores de FDN, FDA, LIG, CT, CEL, PB e EE, e positivamente nos teores de CNF e MM. A utilização do aditivo melhorou os coeficientes de DIVMS e foi capaz de manter até 72 horas. Houve decréscimo nos coeficientes de DIVFDN e DIVFDA com a adição de óxido de cálcio. O óxido de cálcio tem capacidade de hidrolisar a fração fibrosa como também conservar a cana-de-açúcar já picada. As doses 0,5 e 1,0% de cal, apresentaram resultados semelhantes às doses superiores, não havendo necessidade de utilização de doses mais elevadas na hidrolise da cana-de-açúcar. Com o decorrer do tempo ocorre deterioração da cana-de-açúcar, porém esta é menor quando tratada com óxido de cálcio.
Composição bromatológica e digestibilidade in vitro da cana-deaçúcar in natura hidrolisada com óxido de cálcio (CaO)
Keywords: Alkali treatment; Food analysis; Hydrolysing agent; Hydrolysis; Saccharum officinarum; Agente hidrolizante; |Análise de alimento; Hidrólise; Saccharum officinarum; Tratamento alcalino